Dermo-facial reconstruction of a canine with bilateral upper lip avulsion: Case report - Reinstein, Rainer (Pubvet, 2021)
Reconstructive surgery uses tissue redistribution to treat traumatic skin defects, when primary closure is not possible. They result in reduced infections, in addition to greatly facilitating the management of the wound. Facial injuries in dogs, mainly in the muzzle, have little adjacent skin, which makes restorative surgery a surgical challenge. Thus, this work reports the case of a dog seen at the Veterinary University Hospital of the Federal University of Santa Maria (HVU-UFSM), presenting bilateral lesion in the upper lip and nasal plane, with considerable loss of tissue, but which culminated in good aesthetic and functional results after reparative surgery.
Keywords: Reconstructive surgery; veterinary; nasal plane